2017
DOI: 10.1016/j.annemergmed.2017.07.251
|View full text |Cite
|
Sign up to set email alerts
|

273 Emergency Providers Did Not Adequately Manage Patients With Spontaneous Intracranial Hemorrhage and Suspected Intracranial Hypertension

Abstract: addressed interventions were imaging studies (11 items; 29%) and use of antibiotics (9 items; 24%). Recommendations with the 10 highest overall ratings are shown in the Table ; due to a 4-way tie for 10th place, 13 items are included. Within this group, six items address imaging studies, including four that address imaging in children. Another five items focus on antibiotic use, including two regarding respiratory infections and another two regarding asymptomatic bacteruria.Conclusions: 38 CW recommendations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Unfortunately, recent studies have shown that more than half of such patients do not receive adequate management such as blood pressure control prior to transfer. 9 This has placed greater emphasis on earlier and more aggressive blood pressure management in neurocritical care units. 3 The past few decades have seen a dramatic increase in laboratory and clinical research which has guided both medical and surgical management.…”
Section: Initial Diagnosis and Medical Managementmentioning
confidence: 99%
“…Unfortunately, recent studies have shown that more than half of such patients do not receive adequate management such as blood pressure control prior to transfer. 9 This has placed greater emphasis on earlier and more aggressive blood pressure management in neurocritical care units. 3 The past few decades have seen a dramatic increase in laboratory and clinical research which has guided both medical and surgical management.…”
Section: Initial Diagnosis and Medical Managementmentioning
confidence: 99%